1983
DOI: 10.1364/ao.22.002356
|View full text |Cite
|
Sign up to set email alerts
|

Excess loss of single-mode jacketed optical fiber at low temperature

Abstract: This paper describes excess loss of single-mode jacketed optical fibers at low temperature. A structural model is proposed for the jacketed fiber in order to investigate the relationship between the structure and excess loss. This model clarifies the excess loss increase mechanism that any initial irregularity existing in the jacketed fiber increases due to shrinkage of the jacket and causes excess loss. These results show that reducing the buffer diameter and controlling the fiber deformation inside the jacke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…Some recommendations for the selection of the thicknesses and material characteristics a r e presented. The numerical examples a r e executed for silicone/ nylon coated systems, which were studied experimentally by Katsumally induced microbending in dual-coated optical fibers, with an em- , [14]. The theoretical prediction agrees well with the experimental observations.…”
Section: Effect Of Initial Curvature On Low Temperaturesupporting
confidence: 55%
See 1 more Smart Citation
“…Some recommendations for the selection of the thicknesses and material characteristics a r e presented. The numerical examples a r e executed for silicone/ nylon coated systems, which were studied experimentally by Katsumally induced microbending in dual-coated optical fibers, with an em- , [14]. The theoretical prediction agrees well with the experimental observations.…”
Section: Effect Of Initial Curvature On Low Temperaturesupporting
confidence: 55%
“…The numerical examples are executed for silicone/nylon coating systems, studied by Katsuyama et al [lo], and Yabuta et al [14], and discussed by Lenahan [15]. The spring constant K was evaluated by the Vangheluwe formula [17], which for the case in question, when the Poisson ratio of the primary coating material is close to 0.5, can be simplified as follows:…”
Section: Numerical Examplesmentioning
confidence: 99%
“…In the silicone/nylon coatings of Yabuta et al, 6 thicker primaries were asso ciated with substantially more added loss at low temperatures. Cal culations in Section III showed that the coating with thin primary and low added loss at -40°C needs about four times as much strain to buckle as the one with thick primary and high added loss at -40°C.…”
Section: Discussionmentioning
confidence: 92%
“…Any eccentricity of the jacket however can generate fiber microbending and any defects in the coat integrity or even fluctuations in coating diameter can exaggerate this effect [22]- [24]. For example, when a "soft-hard" combination such as nylon 12 on silicone resin has been used, and axial contraction can occur in the stronger hard coating.…”
Section: Tight Designmentioning
confidence: 99%